If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -6 + -1x + -3 = 0 Reorder the terms: -6 + -3 + -8x + -1x = 0 Combine like terms: -6 + -3 = -9 -9 + -8x + -1x = 0 Combine like terms: -8x + -1x = -9x -9 + -9x = 0 Solving -9 + -9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -9x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -9x = 0 + 9 -9x = 0 + 9 Combine like terms: 0 + 9 = 9 -9x = 9 Divide each side by '-9'. x = -1 Simplifying x = -1
| y=4x^2-3x-10 | | y^2-5y-6y+30= | | 12=5-x-6x | | x^2-6x+2x-3=9x+27 | | Y=-2(X^4+2X^2)+8 | | 0.66666a+1=11 | | (k+3)+(k+k-11)+k=64 | | 4y=2(y-5)-5 | | 8b=216 | | 3(4x-3)=5-2x/4 | | 6w+9=18w-3w+81 | | -2V+r=2k | | X-12y=-62 | | 0.5=-0.6ln(x)+1 | | y-49=-2 | | 86-2x=6-10x | | 1/x^3=0 | | 0=x-4+3x | | 1/x^3 | | 2xy+3z+1=0 | | x-3-8x-6= | | 5x-2=13x-19 | | 5w^2-30w+40=0 | | 80-5x+4x+10+80=180 | | -6(4y)= | | 6u+6(u-6)=36 | | 4x+10+80-5x=180 | | 13d^2-7d=0 | | -x+17y=127 | | 4(2x-1)-(-3+7)= | | 2y+9=4y-3 | | -1-7x=36x+6(-7-x) |